THE RELATIONSHIP BETWEEN DISEASE BURDEN, CARE SETTING, AND LIFE-SUSTAINING TREATMENT CHOICES. (11th November 2018) - Chen, E; Pu, C T; Ragland, J; Schwartz, J; Fairbanks, M; Mutchler, J E
Abstract: Life-sustaining treatment preferences were collected from 593 Medical Orders for Life-Sustaining Treatment forms (MOLST) at three hospitals. Logistic regression models estimated the odds for choosing All Treatment (aggressive) vs. Limitations to Treatment for patients with high illness burden (Charlson Score>5 vs. ≤5), controlling for decision-maker (patient/proxy), clinician type, and patient demographics. Over one-third (36%) chose All Treatment. Mean Charlson Score was 8 (SD=3). Proxy decision-makers signed 43% of the forms. Mean patient age was 71 (SD=15); 49% were male, and 83% were non-Hispanic White. Palliative care clinicians administered 50%, and both non-palliative and palliative MDs administered 52% of the MOLSTs. Patients with Charlson>5 were 70% (OR=0.31; p≤0.001) less likely to choose All Treatment than those with Charlson ≤5, controlling for only patient characteristics (pseudo R2=0.148; p≤0.001). Care settings with palliative care clinicians attenuated the magnitude of the relationship between illness burden and life-sustaining treatment preferences (OR=0.54; p≤0.10)(pseudo R2=0.431; p≤0.001).